(untitled) (Zaporizhzhia Historical Review, 2021)
The article depicts the resonance subject in the society ñ the subject of the evangelic-missionary activities of the late protestants in Ukraine. It gives the analysis of both home and foreign element of the missionary and the reaction of the Ukrainian state and society on it. The article demonstrates the stabilityof the evangelic strategy of the late protestants, the confession peculiarities of its execution, the sensible respond to the new social spiritual challenges.